Angiogenesis in the Development of Medication-Related Osteonecrosis of the Jaws: An Overview - Andreas Max Pabst; Maximilian Krüger; Sebastian Blatt; Thomas Ziebart; Roman Rahimi-Nedjat; Elisabeth Goetze; Christian Walter (MDPI AG, 2016)
Medication-related osteonecrosis of the jaws (MR-ONJ) is one of the most relevant side effects of bisphosphonate therapy; it is clinically defined as a non-healing wound in combination with an avascular and necrotic jaw within ongoing bisphosphonate therapy or after completed bisphosphonate therapy. Different theories concerning the development of MR-ONJ have been reported, while the exact pathophysiology is still unknown. Recent studies have increasingly focused on angiogenesis and revascularization concerning MR-ONJ pathophysiology, which seems to be a relevant factor in the development of MR-ONJ and a possible and promising point of action for MR-ONJ prevention and therapy. Therefore, and with respect to the different aspects and specific forms of angiogenesis, the enclosed review summarizes the possible role of angiogenesis and revascularization in the pathophysiology of MR-ONJ. Special focus is given to the strong negative influence of bisphosphonates on progenitor and mature endothelial cells in vitro as well as on microvessel sprouting in vitro and in vivo, which might result in overall reduced wound healing of oral soft and hard tissues, and therefore in an exposed and avascular jaw from a clinical viewpoint. Further, it will be summarized whether and in what way the aspect of angiogenesis might be used for possible MR-ONJ prevention and therapy.